If Sin A + sin³A = cos²A, Prove that : cos^6A - 4cos⁴A + 8cos²A = 4
Answers
Answered by
6
To prove, cos^6A-cos^4A+8cos^2A=4
we will take given equation, and we will try to convert it in whole cos term equation
so we have,
==> sinA+sin^3A =cos^2A , squaring both side we get
==> (sinA+sin^3A)^2 =(cos^2A)^2
==> sin^2A +2sin^2sinA*sin^3A +(sin^3A)^2=cos^4A
==> sin^2A +2sin^2sinA*sin^3A +(sin^3A)^2
now you can find the given answer....
we will take given equation, and we will try to convert it in whole cos term equation
so we have,
==> sinA+sin^3A =cos^2A , squaring both side we get
==> (sinA+sin^3A)^2 =(cos^2A)^2
==> sin^2A +2sin^2sinA*sin^3A +(sin^3A)^2=cos^4A
==> sin^2A +2sin^2sinA*sin^3A +(sin^3A)^2
now you can find the given answer....
Answered by
7
Answer:
AStep-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/ddd/5f5d62f85bfb9d9252b73e9f7c10237f.jpg)
Similar questions